PROCEDURE FOR DETERMINING THE COMPONENTS OF THE STRAIN TENSOR OF THE INHOMOGENEOUS CRUST FROM REPEATED GEODESIC MEASUREMENTS - Fotiadi E.E.; Kuchay V.K.; Keselman S.I. (My University, 1989)
We have recently developed a method in which the spatial components of the strain and displacement tensors are determined in a model of an inhomogeneous crust and have developed algorithms from them, which we describe in detail in this article. We note at the outset that one of the main principles of continuum mechanics is the postulate of small deformations or strains (in repeated geophysical observations, the strain practically never exceeds 10 -3). Strains and displacements of measurable and often considerable height and length on the surface of the inhomogeneous crust are analyzed in terms of the mean strain tensor. The procedures for determining the components of the strain and displacement tensors along faults at the surface of the crust are now implemented in a program package for the BESM-6 computer and have been tested in several tectonically active zones where repeated vertical and linear geodesic measurements have been made.